Urgensi Perlindungan Hukum Investor melalui Klausul Kewajiban Pengungkapan Keberlanjutan dalam Perjanjian Investasi Startup di Indonesia - Safitri Ramadhani; Albertus Sentot Sudarwanto (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the legal protection of investors through sustainability disclosure obligation clauses in startup investment agreements in Indonesia. This research employs a normative legal research method utilizing a statutory approach and a case approach through library research. The findings indicate that the incorporation of sustainability disclosure obligation clauses in startup investment agreements in Indonesia is necessary to address the existing regulatory vacuum, prevent information asymmetry, protect investors through preventive risk management and reinforce the legal standing for breach of contract claims under the Civil Code.